Separatism in the Philippines: Islamist Terrorism, National Liberation or the Struggle for Resources? - A. D. Dikarev (Международная аналитика)
The article highlights the history of separatist activities in the territory of Philippines, the struggle of Muslim minority inhabiting southern regions of the country, for autonomy and independence. This struggle has a constant trend to turn into military clashes with government troops and terrorist actions. The differences in the programs and actions of various political organizations of local Muslims are elucidated as well as ongoing attempts of the Philippine government to create Autonomous Region of the Muslim Mindanao, and most recently – larger Bangsamoro autonomy what will evidently demand changes in the constitution of the Unitarian republic in the direction of federalization. In conclusion the article briefly describes the aggravation of situation in the South of Philippines due to the growing importance of “Islamic factor” and activities of international terrorism in the modern world.